2013
DOI: 10.1021/nl4017072
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanovesicle-Bioactive Conjugates Prepared by a One-Step Scalable Method Using CO2-Expanded Solvents

Abstract: The integration of therapeutic biomolecules, such as proteins and peptides, in nanovesicles is a widely used strategy to improve their stability and efficacy. However, the translation of these promising nanotherapeutics to clinical tests is still challenged by the complexity involved in the preparation of functional nanovesicles and their reproducibility, scalability, and cost production. Here we introduce a simple one-step methodology based on the use of CO2-expanded solvents to prepare multifunctional nanove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 40 publications
2
84
0
Order By: Relevance
“…33 Ethanol and nonencapsulated BNZ were removed by diafiltration of nanovesicular suspensions. CDs loaded with BNZ were prepared by an antisolvent precipitation with compressed CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…33 Ethanol and nonencapsulated BNZ were removed by diafiltration of nanovesicular suspensions. CDs loaded with BNZ were prepared by an antisolvent precipitation with compressed CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Dye‐loaded QSs can be prepared by a one‐step method using compressed CO 2 , named depressurization of expanded liquid organic solution‐suspension (DELOS‐SUSP), showing several advantages over conventional routes for the preparation of functionalized vesicles. Indeed, it is a green technology leading in a single step to the formation of multifunctional nanovesicles with superior structural homogeneity . As dye models, we used lipophilic fluorophores with long alkyl chains, which can be integrated into QS membrane exploiting hydrophobic interactions between the chains of the dyes and the hydrophobic compartment of the double‐layer membrane.…”
mentioning
confidence: 99%
“…DiD‐loaded QSs with DID loadings, L = moles DID /(moles CTAB + moles Cholesterol ), ranging from 0.6 × 10 −3 to 6.6 × 10 −3 (Table S1, Supporting Information) were prepared using the DELOS‐SUSP methodology . The physicochemical properties of the resulting vesicles with L = 1.3 × 10 −3 (D‐QS‐2) are here compared with those of other DiD‐loaded QSs obtained by other methods generally used for the preparation of loaded vesicles, such as incubation (D‐QS‐2‐IC), sonication (D‐QS‐2‐SON), and thin‐film hydration (D‐QS‐2‐TFH) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, nanoliposomes loaded with GLA were introduced to effectively deliver the recombinant protein to primary Fabry cells. It was demonstrated that the carried enzymes exhibited a higher specific activity and better enzymatic performance than free administered enzymes …”
Section: Introductionmentioning
confidence: 99%